Wind farm operation during important disturbances in electric power system - Grzadzielski, I.; Welenc, R.; Plucinski, T. (Видавництво Національного університету «Львівська політехніка», 2007)
In the paper, the selected results of simulation studies on the electric power system’s dynamic conditions in the area with high density of the wind farms are presented. In simulations, the GE – PSLF software package has been used. The computing models of Polish power system have been applied. The advantages of new solutions for the wind power plants operation during system’s disturbances due to faults have been shown. The role of the cooperating SVC-type FACTS devices has been indicated. The still existing threat to the system operation due to the uncontrolled increase in the power of connected wind farms has been underlined.